Lymphoproliferative Disease of the Orbit. Issue 2 (March 2015) - Li, Emmy Y.; Yuen, Hunter K.; Cheuk, Wah
<x xml:space="preserve">Abstract</x> Abstract Lymphoproliferative diseases of the orbit account for majority of orbital tumors. The pathologies range from reactive lymphoid hyperplasia to specific IgG4-related inflammation to malignant lymphomas. This review summarizes current concepts regarding pathology, clinical presentation, diagnosis, staging, and treatment strategies of major orbital lymphoproliferative diseases based on updated and relevant bibliography.